ANALISIS CAMPUR KODE PADA PERCAKAPAN MASYARAKATA DI DESA SISOBAHILI KECAMATAN SUSUA KABUPATEN NIAS SELATAN - Laia, Yoniman (Universitas Nias Raya, 2024)
This research was motivated by the code mixing of the Nias regional language and Indonesian in the conversations of the people of Sisobahili village, Susua District, South Nias Regency. This research aims (1) to describe the forms of code mixing in community conversations in Sisobahili village, Susua District, South Nias Regency (2) to determine the factors behind the occurrence of code mixing in community conversations in Sisobahili village, Susua District, South Nias Regency. The approach used in this research is a qualitative approach with descriptive research type. The research findings obtained by researchers are forms of code mixing in the conversations of the people of Sisobahili village, Susua District, South Nias Regency in the form of words, phrases, bastards, repetition of words, expressions/idioms and factors that cause code mixing in the conversations of the people of Sisobahili village, Susua District, Regency. South Nias in the form of role identification, variety identification, and the desire to explain/interpret. So it can be concluded that the forms of code mixing that occur in the conversations of the people of Sisobahili village, Susua District, South Nias Regency are in the form of words, phrases, bastards, repetition of words and expressions/idioms and the factors causing the emergence of code mixing in the conversations of the people of Sisobahili village, Susua District, South Nias Regency in the form of role identification, variety identification, the desire to explain and interpret, the researcher suggests to students that this research can be used as a basis for further research in the field of sociolinguistics for language teaching, for society, so that this research can increase society's insight or realize that mixed use code can cause the extinction of the Nias regional language, for readers, the use of code mixing is not good when communicating. Everyone should be able to use the correct language or use the real language and let's preserve the Nias regional language so that it doesn't perish and disappear.